2011
DOI: 10.1007/s00011-011-0422-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma levels of heparin-binding protein in patients with shock: a prospective, cohort study

Abstract: HBP is elevated in patients with shock from septic and non-septic etiologies. Future investigations are required to define the functional role of HBP in patients with shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 16 publications
7
52
1
Order By: Relevance
“…In addition, the difference in HBP levels between infected and non-infected patients with ALI/ARDS was not significant, and neither was the difference in patients with septic and nonseptic shock. Our results are consistent with previous research demonstrating that HBP levels were notably enhanced in patients with shock regardless of whether they suffered from sepsis or not [24]. This is supported by the viewpoint that not only bacterial products [25] but also nonbacterial cross-linking of β 2 -integrins on the surface of neutrophils is sufficient to trigger HBP secretion [1].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the difference in HBP levels between infected and non-infected patients with ALI/ARDS was not significant, and neither was the difference in patients with septic and nonseptic shock. Our results are consistent with previous research demonstrating that HBP levels were notably enhanced in patients with shock regardless of whether they suffered from sepsis or not [24]. This is supported by the viewpoint that not only bacterial products [25] but also nonbacterial cross-linking of β 2 -integrins on the surface of neutrophils is sufficient to trigger HBP secretion [1].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, another study showed that HBP levels did not correlate with survival in nonseptic and septic shock patients [24]. HBP has been shown to increase the survival of cultured monocytes and protect them from oxidative stress [4,26].…”
Section: Discussionmentioning
confidence: 99%
“…Both HBP and MPO peaked during CPB but had a rapid decline. The levels were still high four hours after surgery, with levels comparable to those measured during septic conditions 124,151,152 .…”
Section: Heparin Reversal With Protaminesupporting
confidence: 48%
“…HBP is a multifunctional protein mainly released from activated neutrophils 123 . During systemic inflammation plasma levels of HBP increases 124 . HBP exerts pro-inflammatory effects 125 and is a potent inducer of vascular permeability and leukocyte recruitment 126 which are considered to contribute to organ injury and organ dysfunction.…”
Section: Fibrinolysismentioning
confidence: 99%
“…Heparin-binding protein has been reported as a potential biomarker of severe sepsis and septic shock (Linder et al, 2009, 2012; Chew et al, 2012) and as an indicator of vascular leakage (Johansson et al, 2009). A comparison of serum HBP levels between patients with S. suis -associated STSS versus patients without STSS or healthy individuals revealed that the serum HBP levels in patients with STSS were significantly higher than those in patients with meningitis or healthy controls (46.61 ± 9.49 ng/mL vs. 11.52 ± 5.20 ng/mL or 1.84 ± 0.96 ng/mL, respectively; P = 0.0007, Figure 1 ), which suggested that HBP is released during the progression of STSS in patients infected with S. suis .…”
Section: Resultsmentioning
confidence: 99%